Handbook of public policy analysis theory, politics, and methods - Fischer, Frank 1942-; Miller, Gerald; Sidney, Mara S. 1964- (Public administration and public policy, 2007)
Covers the historical development of policy analysis, its role in the policy process, and empirical methods. This book considers the theory generated by these methods and the normative and ethical issues surrounding their practice. It deals with the basic origins and evolution of public policy. It examines the stages of the policy-making process.